Aspiration pneumonia and anesthesia techniques in hip fracture surgery in elderly patients: A retrospective cohort study using administrative data. (24th January 2022) - Fukuda, Taeko; Imai, Shinobu; Shimoda, Shunji; Maruo, Kazushi; Nakadera, Masaya; Horiguchi, Hiromasa
Purpose: Aspiration pneumonia is a critical issue. General anesthesia may suppress the airway's protective reflex. However, aspiration pneumonia is also observed in patients who undergo hip fracture surgery under spinal anesthesia. The aim of this study was to investigate the relationship between anesthesia methods and aspiration pneumonia as well as the predictive factors of aspiration pneumonia in elderly patients undergoing hip fracture surgery.Methods: The medical records of 19, 809 patients aged ≥60 years who underwent hip fracture surgery under general or spinal anesthesia were reviewed. After propensity score matching, the anesthesia methods affecting the occurrences of aspiration pneumonia and other complications were investigated via logistic regression and instrumental variable analyses. Predictive factors of aspiration pneumonia were also investigated in all subjects using a multivariable logistic regression analysis.Results: Among the 11, 673 general anesthesia patients and 8136 spinal anesthesia patients, aspiration pneumonia occurred in 356 patients (1.8%). Post-propensity score matching the incidences of aspiration pneumonia with general and spinal anesthesia were 1.8% and 1.5%, respectively ( p = 0.158); other pulmonary complications were 1.5% and 1.5%, respectively ( p = 0.893); and the mortality rates were 1.4% and 1.2%, respectively ( p = 0.219). The predictive factors of aspiration pneumonia were advanced age, male sex, lean body, cerebrovascular disease, dementia, and dependency for activities of daily living (eating).Conclusion: Spinal and general anesthesia showed similar incidences of aspiration pneumonia in elderly hip fracture surgery. Regardless of the anesthesia method, great care should be taken, especially in elderly patients with the identified predictive factors.